Parent reported longstanding health problems in early childhood: a cohort study. Issue 7 (1st July 2003) - Spencer, N; Coe, C
Abstract : Aim: To study changing prevalence and correlates of longstanding health problems across early childhood. Methods: Of 2576 infants enrolled in the Coventry Cohort Study at birth, parents of 2157 at 8 weeks, 1752 at 8 months, 1521 at 18 months, and 1182 at 3 years completed the Warwick Child Health and Morbidity Profile. Results: The prevalence of parent reported longstanding health problems was 4.3% at 8 months, 6.9% at 18 months, and 9.7% at 3 years. Congenital anomalies accounted for 42.1% of longstanding health problems at 8 months, 40.0% at 18 months, and 27.8% at 3 years. The proportion accounted for by asthma was 17.1% at 8 months, 21.9% at 18 months, and 24.3% at 3 years. In each age period, children reported to have longstanding health problems were at increased risk of impaired functional health, poorer general health, and reduced health related quality of life. Low birthweight infants were most at risk of longstanding health problems at 8 months. By 3 years, risk of longstanding health problems was associated with living in rented accommodation and living in a smoking household. Conclusions: The prevalence of parent reported longstanding health problems increased across early childhood. Congenital anomalies constituted the major cause, particularly in infancy, with asthma and developmental delay becoming more prominent by 3 years of age. Social patterning of longstanding health problems and the association with smoking were clearly established by 3 years of age but the relation may have been mediated by low birth weight earlier in infancy.